Job Satisfaction Among Dentists According to Workplace in Tehran - Reza Emrani; Katayoun Sargeran; Ahmad Reza Shamshiri; Hossein Hessari (Tehran University of Medical Sciences, 2021)
Objectives: The purpose of the present study was to assess the level of job satisfaction among dentists in Tehran, according to background determinants, working environment elements, and type of workplace in 2018. Materials and Methods: In this cross-sectional study, 350 dentists, selected by convenience sampling, completed a validated Persian job satisfaction questionnaire in a dental congress (with about 1100 participants) in Tehran, and in 59 dental clinics. The questionnaire included 39 structured questions (in 12 domains) on job satisfaction, reporting the satisfaction level according to a 5-point Likert scale. The level of satisfaction was measured by summing the weighted scores of each domain. The mean job satisfaction score (out of 100) was reported according to demographic factors (age, gender, level of income, years of experience, marital status, and number of children), working environment elements (number of assistants, number of colleagues, type of workplace), and stress score (8 questions). Linear regression was applied for statistical analysis. Results: The mean score of job satisfaction was 70±10. The analysis showed that women, dentists with a low income, those working in the public sector, and those with higher stress scores had lower job satisfaction scores (P<0.05). The number of dental assistants, number of colleagues, age, work experience, marital status, number of children, and monthly number of patients had no significant correlation with job satisfaction (P>0.05). Conclusion: The level of job satisfaction was mainly related to individual determinants. Improving job satisfaction can foster the whole dental care system and working environment elements.